PERENCANAAN AGREGAT KAOS SABLON PADA CV.PERCETAKAN X DENGAN HEURISTIC - Yusnia Sinambela (Universitas Quality, 2022)
CV.X is a company engaged in the printing sector. The main production is screen printing t-shirts because the demand is always there and increases every month. This company determines demand in the next period only with data from the previous period. The demand for t-shirts is the highest demand from other graphic products. This company has not implemented production planning by trial and error for the implementation of its production. In this study, a production plan will be analyzed and proposed by adjusting the production level, labor requirements, inventory, overtime, sub-contracts and all variables that can be controlled by the company. The demand approach for the next period is carried out using the exponential forecasting method and the aggregate planning calculation using the Heuristic method. The results obtained from forecasting with the value of Mean Absolute Percentage Error (MAPE) Exponential Method = 0.94. The cost of calculating the Labor Control Method is 28,654,800, the cost with labor control is 28,654,800, the cost with Mixed with Sub Contracts is 28,007,969.1, so the planning method is chosen with a mix of sub contracts